Features of design and development of children's countryside recreation camps - Belonogova Kristina A. (Архитектон)
Issues in children’s health protection, education and all-round development are given much attention around the world. These issues tend to be addressed comprehensively at all levels of the state system. Children’s recreation camps and the systems of such camps are undergoing modernization in accordance with current trends and needs. During the Soviet period, the main type of children’s recreation facilities was “Pioneer” summer camps. Current trends in this area are different, but 50% of the modern camps are of the “Pioneer” camp type or occupy the sites of former camps. The article examines modern trends in the spatial design and plan of children's camps, reviews regulatory documents and guidelines, and overviews international and domestic experiences in children's camp design and planning. A classification of children's camps is suggested, and camp planning features are identified.